Predictors and prognoses of new onset post-stroke anxiety at one year in black Africans (2020)
Background: There is relatively limited information on the risk factors and outcome of new onset Post stroke Anxiety (PSA) in Low- and Middle-Income Countries. We estimated incidence, cumulative incidence, risk factors and outcome of new onset anxiety in the first year of stroke among African stroke survivors. Methods: We analyzed the dataset of a completed clinical trial comprising patients enrolled to test an intervention designed to improve one-year blood pressure control among recent ( one month) stroke survivors in Nigeria. Anxiety was measured using the Hospital Anxiety and Depression Scale. Outcomes were assessed using the modified Rankin Scale (mRS), Community screening instrument for dementia (CSID) and Health Related Quality of Life in Stroke Patients (HRQOLISP-26). Results: Among 322 stroke survivors who were free of anxiety at baseline, we found a one-year cumulative incidence of 34% (95% CI = 28.6 39.3). Rates were 36.2% (95% CI =29.6 42.7) for men and 29.2% (95% CI =19.9 38.3) for women. In multivariate Cox regression analyses, haemorrhagic stroke type was associated with higher risk of new onset PSA (Hazard Ratio=1.52, 95% CI =1.01 2.29). New onset PSA was independently associated with cognitive [(mean difference (MD) in CSID scores=1.1, 95% C.I=0.2, 1.9)] and motor decline (MD in mRS scores= 0.2, 95% C.I= 0.4, 0.02), as well as poorer quality of life overtime (MD in total HRQOLISP-26 scores=3.6, 95% C.I=1.0, 6.2). Conclusion: One in 3 stroke survivors in Nigeria had PSA at one year. Clinicians in SSA should pay special attention to survivors of haemorrhagic stroke as they are at higher risk of incident anxiety and therefore its consequences.